Pelatihan Produksi Konten Pembelajaran Kreatif untuk Guru PAUD HIMPAUDI Kecamatan Kedungwuni - Ari Putra Wibowo; Devi Sugianti; Arief Soma Darmawan (Jurnal Kabar Masyarakat, 2026)
The rapid development of digital technology has encouraged educators to utilize learning videos as an effective medium to support teaching and learning activities. However, many early childhood education (PAUD) teachers still have limited knowledge regarding video production techniques, including camera settings, shooting angles, lighting arrangements, and video aspect ratio adjustments suitable for social media platforms. This community service activity aimed to improve the competencies of PAUD teachers in producing creative and engaging learning video content. The activity was conducted on May 21, 2026, at KB Bukit Bakat Ambokembang, Kedungwuni, involving 60 teachers from various PAUD institutions under HIMPAUDI Kecamatan Kedungwuni. The methods employed included lectures, workshops, hands-on practice, and mentoring sessions. Training materials covered basic video camera settings, lighting techniques, camera angles, video composition, aspect ratio adjustments, and video editing using CapCut. The results showed that participants gained a better understanding of video production concepts and were able to produce ten learning videos collaboratively. Participants demonstrated increased confidence in creating educational content tailored to the characteristics of social media platforms. This activity contributed to strengthening teachers’ digital literacy and creative content production skills to support more engaging learning experiences.